2002
DOI: 10.1093/humrep/17.2.341
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the depth of embryo replacement into the uterine cavity on implantation rates after IVF: a controlled, ultrasound-guided study

Abstract: The depth of the embryo replacement into the uterine cavity may influence implantation rates, and thus it should be considered as an additional procedure among factors recently proposed as associated with successful embryo transfer after IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(52 citation statements)
references
References 35 publications
3
48
0
1
Order By: Relevance
“…Some of these proposed factors include characteristics of the catheter [1], operator experience [2], the site of uterine cavity where the embryo is transferred [3-6], presence of mucus or blood on the catheter following withdrawal [7], uterine contractions secondary to uterine manipulations, and difficulty passing through the cervix [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Some of these proposed factors include characteristics of the catheter [1], operator experience [2], the site of uterine cavity where the embryo is transferred [3-6], presence of mucus or blood on the catheter following withdrawal [7], uterine contractions secondary to uterine manipulations, and difficulty passing through the cervix [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Along with these factors on treatment success, the site of embryo transfer has also been debated by several investigators but lacks a consensus (9)(10)(11)(12)(13). Several studies demonstrated a significant effect of embryo transfer depth on IVF and embryo transfer outcomes (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In early times, it was reported to position the embryo(s) 0.5 cm from the endometrial fundus [31,32,33]. In later years, studies conclude to position the embryo(s) 2 cm from the endometrial fundus [13,18,19]. Most recently, Cenksoy et al [17] reported that the optimal position of the air bubble seems to be a distance of <10 mm from the endometrial fundus, in accordance with Friedman et al [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although about 85% of all couples undergoing IVF or ICSI treatment reach the stage of embryo transfer, only one-third actually becomes pregnant at the end of a treatment cycle (fresh cycles: most recent ESHRE European register: 2009 [4]). Various factors concerning embryo transfer have been described to explain those limited embryo implantation rates: the type of catheter used for the transfer [5,6,7]; including the relevance of a soft distal part on the catheter [8,9], the presence of blood or bacteria on the catheter [10,11]; the experience of the physician [12] and the use of ultrasound guidance [13,14,15,16]. Much of the inefficiency of the embryo implantation may therefore be derived from the embryo transfer technique [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation